Migrant Workers’ Child Care Style in Cilacap District - Urip Tri Wijayanti; Dwi Purwaningsih (Randwick International of Social Science Journal, 2020)
The Migrant workers in Cilacap District are dominated by women who are married, so that the care of the children is carried out by the father. This research aims to examine the father's parenting. This research uses a qualitative approach. It uses Purposive selection to find the informants. The Informants include father, wife/ mother, secondary family (grandfather, grandmother, and siblings). Data were collected by interview, observation and documentation. The results of the study were two kinds of care, some were delegated to secondary families. For example grandparents or other relatives and some were cared for by their husbands/ fathers. However, in general the care is delegated to secondary families. The reason is because the husband/ father does not have parenting experience. The parenting pattern applied by secondary families / grandparents applies permissive and democratic parenting. Then for those who are cared for by their husbands / fathers themselves apply a democratic parenting pattern. Where parents are warm and affectionate to children. Parents, especially fathers, explain why children should not do something. For care for adolescents, care is done by the husband/ father himself. The pattern of parenting that is applied uses permissive and democratic patterns. BKKBN recommendation needs to carry out parenting training for fathers, so that female migrant families do not delegate care to secondary familie